A different type of acute myocarditis: a case report of acute autoimmune myocarditis mediated by anti-PD-1 T lymphocyte receptor (pembrolizumab). Issue 5 (4th October 2020) - Salido Iniesta, Mario; López López, Laura; Carreras Costa, Francesc; Sionis, Alessandro
Abstract: Background : Pembrolizumab is an immune check-point inhibitor (ICI), which acts by blocking the T lymphocyte PD-1 inhibitor receptor. It has been increasingly used in advanced or non-responsive tumours with promising results. However, acute myocarditis is an infrequent but potentially life-threatening autoimmune adverse effect related to ICIs. Case summary : This case deals with a 69-year-old gentleman on second-line therapy with pembrolizumab for advanced non-small cell lung cancer. Three weeks after first dose, the patient was diagnosed with an autoimmune hepatitis, treated with decreasing corticoid dosage, followed by acute heart failure. On admission, his electrocardiogram (ECG) showed diffuse repolarization changes and a transthoracic echocardiography revealed severe left ventricle impairment (left ventricular ejection fraction 32%). High-sensitivity cardiac troponin was elevated and a coronary angiogram was performed showing non-significant obstructive disease. An autoimmune myocarditis was suspected, and high-dose intravenous corticoid, intravenous vasodilators, and loop diuretics were started with favourable response. Cardiac magnetic resonance (CMR) imaging, performed 2 weeks after clinical onset, revealed extracellular oedema in the anteroseptal-apical left ventricle segments. A new transthoracic echocardiography, performed after 3 months, showed preserved left ventricle ejection fraction. Finally, the patient was readmitted due to an autoimmune myasthenia-like syndrome. Discussion : Acute autoimmune myocarditis related to ICIs is a challenging diagnosis and its incidence has been underestimated in early studies. Endomyocardial biopsy (EMB) is the gold standard test for its diagnosis. Nevertheless, a definite myocarditis diagnosis is possible without EMB when characteristic clinical syndrome, elevated myonecrosis markers, and electrocardiographic, echocardiographic, and CMR changes are present together.